Pathogenesis of lung oedema in cattle infected with theileria parva (Muguga). - Maina, P. (Makerere University, 1994)
Packed cell volume were measured by centrifugation for 6 mm. In the Hawksley microhaematocrit using blood collected from the Jugular vein. Haemoglobin estimation expressed as percentage differential white cell counts were made from thinblood smears counting 400 cells per smear were possible using the battlement method of scanning. The superficial lymph node were measured horizontally through the skin with tubercilin testing cappillers. Changes in lymph nodes as seen in biopsy smears throughout the course, were characteristic of the disease. Between Day T -5 and T-2 the proportion of small lymphocytes decreased and the proportions of large lymphocytes and primitive cells increased. Between Day T - 1 and T + 1 the changes became more marked with a further increase in the proportion of large and primitive cells. At this stage blast cells with deeply basophilic cytoplasm became prominent in the smears. These were morphologically similar to plasmablasts and piroplasmacytes, and it was in these, that the earliest visible forms of the parasite were seen, appearing as small comparatively Pale areas in the cytoplasm within which were distinct pink staining bodies. Sera from Theileria parva Muguga infected, recovered and rechalleged cattle were tested in complement dependent cytotoxicity, membrane immunofluorescence and antibody dependent cellular cytotoxicity assays for the presence of antibodies against cell membrane antigens of T. Parva transformed cell lines. In the complement dependent antibody - mediated cytotoxicity assay, sera from healthily infected animals were negative. Some recovered cattle showed a positive reaction, but such reactions were also observed when an Bos-taurus cell line infected with T. parva (Muguga) and against Ig negative peripheral blood leucocyte. Evidence is presented that these reactions could be evoked by attachment of immune complexes to Fc-receptors. It is concluded that cattle exposed T. parva infection do not develop antibodies against specific T. parva (or T. parva -induced) cell surface antigens. C3a anaphylatoxin (C3a> induces smooth muscle contraction, enhances vascular permeability, and stimulates mast cell histamine release. This factor is a postulated mediator in sensitivity reaction characterized by angio oedema and or urticaria. These symptoms have been observed in sensitive individuals after oral administration of a radioimmunoassy (RIA) was employed to quantitative variations ( 0 - 1000 ng/ml in plasma C3a levels during acute sensitivity reactions were produced by Kl. (Elevation of plasma C3a levels in 3K1 sensitive patients correlated temporally with appearance of Kl induced urticaria. Conversely C3a levels remained unchanged or even declined in 7 non-sensitive controls (3 with angi oedema, 3 with chronic urticaria, and 1 with vasculitic purpura) after Kl administration. Although plasma C3a levels were elevated during the sensitivity reaction, functional measurements of C2C3C5, total hemolytic complement as well immunochemical determination of C3 and C4 and factor B did not change significantly. The observations indicate that the C3a RIA provides a more sensitive measure of C3 conversion than conventional techniques. C3a is generated during this type of sensitivity reaction. This results suggest that the anaphylatoxins may play a significant role in the pathogenesis of lung oedema and other sensitivity reactions.